Nest visits and capture events affect breeding success of Yellow-billed and Pacific loons. (28th January 2015) - Uher-Koch, Brian D.; Schmutz, Joel A.; Wright, Kenneth G.
Abstract: Accurate estimates of breeding success are essential for understanding population dynamics and for managing populations. Unfortunately, research activities to collect these data can negatively impact the breeding success of the study species and bias estimates of breeding success. Despite the potential for negative impacts, few studies have documented the effect of capturing incubating adults on nest survival or compared nest survival following different capture methods. In this study we evaluate the impacts of investigator disturbance associated with captures and nest visits on nest survival of Yellow-billed Loons ( Gavia adamsii ) and Pacific Loons ( Gavia pacifica ) in the National Petroleum Reserve-Alaska (NPR-A), an area of conservation concern, in 2011–2013. In an effort to reduce capture-related nest failures, we developed a new suspended dive net technique to catch territorial aquatic birds while off their nests. We then compared nest survival following suspended dive net captures to bow-net trap captures of breeding adult loons. Daily nest survival following bow-net trap or suspended dive net capture was about 30% lower than when adults were not captured. The effect of captures on nest survival was similar between bow-net trap and suspended dive net capture methods. Nest visits without captures also negatively impacted nest survival, although less than captures. If not accounted for, nest visitation biased daily survival rates of nests downward 6%. Effects of investigator disturbance did not differ by species or between years. Our results suggest that any source of disturbance that displaces incubating adult loons could potentially reduce nest survival. To maximize breeding success, human disturbance factors should be limited near loon nests.